Waste recycling: feasibility of saw dust based spent mushroom substrate and goat manure in vermicomposting - Adi Ainurzaman Jamaludin,; Noor Zalina Mahmood,; Noorlidah Abdullah, (Universiti Kebangsaan Malaysia, 2012)
Vermicomposting for 140 days by using Lumbricus rubellus was conducted after 21 days of natural pre-composting. Five treatments in different ratio of goat manure: spent mushroom substrate were prepared as feed materials with four replicates for each treatment namely; 20:80 (TA), 40:60 (TB), 50:50 (TC), 60:40 (TD) and 80:20 (TE). As for control, each treatment without earthworm was prepared. On the basis of nutrient elements, goat manure and spent mushroom substrate can be decomposed through both methods of vermicomposting and natural composting. Findings of this study indicated that the higher usage of goat manure with longer duration resulted in the production of improved organic fertilizer.